Exploring the co‐benefits of urban green infrastructure improvements for businesses and workers' wellbeing. Issue 1 (7th August 2017) - Cinderby, Steve; Bagwell, Sue
Abstract : Explorations of the benefits for businesses in terms of customer experience or improvements in staff wellbeing from installing and retro‐fitting green infrastructure (GI) in a European city context have been lacking. This paper reports on a two‐year longitudinal mixed methods study in a district of central London evaluating the changes resulting from the installation of a mixture of greening schemes for different types of business sectors and their staff members. Business managers, particularly from retail and leisure sectors, perceived increases in customer footfall and sales in relation to the improvements. Providing accessible green space in office settings led to improvements in morale, team interaction and workplace satisfaction among staff members able to access the improvements. Increased GI was seen as improving uptake of company environmental policies such as energy saving or recycling among staff by their managers. Impacts of neighbourhood GI schemes on staff wellbeing were mixed, with increased greening leading to improved self‐reported workplace happiness and greater interaction with nature spaces but not changes in overall measurements of staff wellbeing. Overall, the findings indicate that GI could represent a worthwhile investment for UK and European businesses through these combinations of direct and indirect returns adding to the known environmental benefits improving urban green spaces can provide.